Strachan-Scott Syndrome: Ayurvedic Perspective (International Journal of Ayurveda and Pharma Research, 2024)
Strachan Scott Syndrome also known as Tropical Ataxic Polyneuropathy (TAN) is a rare neurological disorder characterized by the lesions involving skin and mucous membrane, optic neuropathy and peripheral neuropathy, likely to be caused due to chronic cyanide intoxication following dependency to single plant component, cassava. It is considered as a disease of poor tropical populations but lacks a clear statistics on how many people are affected worldwide, but in affected population prevalence have been noted in more than a quarter. A very little is known about its incidence in India. The clinical spectrum of the syndrome ranges from oculo-oro-genital skin manifestations to severe neurological deficits. This has no direct correlation in classics, though Kalayakhanja which is one of the neurological disorders mentioned under Vatavyadhi, but clinically different in presentation to Strachan Scott Syndrome. This is a disease caused as a result of chronic intoxication of cyanide so etiologically it could be considered under the concepts of Dooshivisha. The signs and symptoms can be considered as the sequential involvement of the Dhatus and Upadhatus, manifesting as a Vatavyadhi as it progresses to involve the nervous system. Being a disease with a very few diagnosed cases and available literatures, this is an attempt in understanding the mechanism of the syndrome from Ayurvedic point of view and the probable management strategies which could be adopted to turn into a manageable one.